The height of watermelons with wall - Extended Abstract - Thomas Feierl (Discrete Mathematics & Theoretical Computer Science, 2007)
We derive asymptotics for the moments of the height distribution of watermelons with $p$ branches with wall. This generalises a famous result by de Bruijn, Knuth and Rice on the average height of planted plane trees, and a result by Fulmek on the average height of watermelons with two branches.